Theoretical Analysis of Surface Active Sites in Defective 2H and 1T′ MoS2 Polymorphs for Hydrogen Evolution Reaction: Quantifying the Total Activity of Point Defects. Issue 3 (21st January 2020) - Ekspong, Joakim; Gracia‐Espino, Eduardo
Abstract: Defect engineering is a common and promising strategy to improve the catalytic activity of layered structures such as MoS2, where in particular the 2H and 1T′ polymorphs have been under intense study for their activity toward the hydrogen evolution reaction. However, the large variety of defects, each with its own distinct and usually unknown effects, complicates the design and optimization of such defective materials. Therefore, it is relevant to characterize in detail the effect of individual defects and to be able to combine these observations to describe more complex materials, such as those seen experimentally. Therefore, nine point defects (antisites defects and vacancies) are theoretically studied on single layer 1T, 1T′, and 2H MoS2 polymorphs, and the variation and spatial distribution in the active sites are identified. It is found that all defective 1T′ monolayers exhibit an increase in the exchange current density of at least 2.3 times when compared to pristine 1T′ MoS2, even if a reduced number of active sites are observed. The results are later used to propose a methodology to study materials containing a mixture of crystal phases, or other alterations that cause inhomogeneous changes in the activity of catalytic sites. Abstract : The inhomogeneous distribution of active sites represents a challenge when designing defective materials for electrocatalysis, making it necessary to both study individual defects and to combine the observations to describe materials with a richer mixture of defects. Therefore, individual active sites are theoretically characterized in defective MoS2 and a methodology to study materials containing a mixture of crystal phases or other lattice alterations is proposed.